PERANCANGAN GAME EDUKASI PEMBELAJARAN BAHASA PEMROGRAMAN JAVA BERBASIS ANDROID - Windy, Windy; Fajrin, Alfannisa Annurrullah (Computer Science and Industrial Engineering, 2023)
Digital education is currently very developed in the field of technology which has learning facilities with educational games so that lessons will be easier to understand and more interesting. while studying the Java programming language is known as learning that teaches the basics of programming languages based on android. while learning at BATAM ADVENT VOCATIONAL SCHOOL uses guidebooks that can be obtained by teachers from the internet using traditional methods making it difficult for students to learn Java, because the teacher only delivers lessons in front of the class and students only listen to the lessons delivered by the teacher. The method used to design educational games for learning the Java programming language based on Android is the Game Development Life Cycle (GDLC) and Unified Modeling Language (UML) methods, making games using Unity. The research is educational games for learning the Java programming language based on Android which can be used as learning media at ADVENT BATAM Vocational Schools, to add insight and knowledge to students about Java programming.